Utilization of GeoGebra software in mathematics learning: A Literature Systematic Review - Seftiana, Gina; Lestari , Nurindah; Isnawan, Muhamad Galang; Rusmayadi, Muh. (Nashir Al-Kutub Indonesia, 2024)
The research aimed to investigate the utilization of GeoGebra software in mathematics education, focusing on how it is integrated into teaching and learning. Employing a systematic literature review method, this study synthesized findings from various academic sources. The results indicated several significant points regarding GeoGebra's application in education. First, GeoGebra software has been effectively used across various mathematical topics, including geometry, algebra, calculus, and other related areas. Its flexibility makes it a valuable tool for visualizing complex concepts and enhancing students' understanding. Second, the utilization of GeoGebra spans both high school and college levels, showing its wide acceptance in diverse educational settings. The software has proven beneficial for learners at different academic stages, allowing them to explore mathematical concepts interactively. Third, the use of GeoGebra has demonstrated positive impacts on students' learning outcomes. It enhances engagement, fosters better comprehension of abstract ideas, and significantly improves students' higher-order thinking skills, such as problem-solving, critical thinking, and creative reasoning. Furthermore, the study revealed that GeoGebra had been widely used in various regions of Indonesia, particularly in the western parts, indicating growing interest in integrating ICT tools in mathematics education. Teachers and educators in these regions have adopted the software to facilitate more dynamic and interactive learning environments. In conclusion, the findings of this study highlight the effectiveness of GeoGebra in improving students' learning outcomes and mathematical thinking skills. Its potential for fostering a deeper understanding of mathematics and enhancing cognitive abilities makes it a valuable resource for educators.